The Double Parallel Curriculum in Palliative Care: Teaching Learners to Teach End-of-Life Care at the Bedside. (November 2017) - Healy, Jennifer; Chappell, Phylliss; Lee, Shuko; Ross, Jeanette; Sanchez-Reilly, Sandra
Context: Dying is a natural process, yet physicians are often uncomfortable caring for dying patients. Learners have limited exposure to curriculum on caring for dying patients and often navigate these encounters without appropriate skills and confidence. We developed and implemented the Double Parallel Curriculum in Palliative Care (DP-PC): End-of-Life (EOL) module. The DP-PC focuses on teaching third-year medical students (MS3) to not only take care of patients in their last hours of life but give learners the confidence to teach patient's families what to expect as they hold vigil at their loved one's bedside. Objectives: To develop and implement an educational intervention that improves learners' knowledge and confidence in EOL patient and family care. To expand learner confidence to a dual level (learners become teachers) with a simplified and culturally sensitive electronic bedside teaching tool designed to guide learners and patients/families conversations. Methods: Curriculum was completed during MS3 ambulatory rotation and included pre-/posttests, an online case-based module, faculty demonstration, and learner role-play using the bedside teaching tool. Results: A total of 247 participants took the pretest, 222 participants took the posttest, and 222 participants matched the pre-/posttest surveys. Students' knowledge of EOL care and the confidence to teach other learners and families about EOL care significantly improved after completing the curriculum. Conclusion: The DP-PC is a technology-savvy educational intervention that improves learner confidence and knowledge toward caring for dying patients and their families. Easy access, technology-based teaching tools may enhance bedside teaching of health-care learners and improve the care of patients and their families at the end of life.